(untitled) (Al-Academy, 2025)
The research problem emerges with the question: Next: What are the representations of sustainable design context in calligraphy production? The research aims to reveal these representations within the spatial boundaries of calligraphy production in Iraq, Saudi Arabia, Turkey and Iran. The theoretical framework addressed the topics of context: meaning, concept, aspects of context - commonality and difference, and the design context between repetition, extinction and sustainability. The third chapter included the research procedures using a methodology that adopted the descriptive analytical approach and a community that included (73) productions, from which (14) models were selected as a sample and analyzed. The research reached the following results: We find that calligrapher works rely on a special design context that can be transferred to another calligraphy type while maintaining the same quality after it stabilizes. Attempts appear to renew, develop, and modify it, either implicitly or entirely. These attempts are innovative systems and contexts that achieve contextual sustainability and continuous contemporaneity for the written product. It is possible to find written contexts and products with a character that is aligned with the goal of achieving a specific purpose through the migration of a system operating within a calligraphy type, such as the labyrinthine system in square Kufic script. This system is incorporated and adapted in design to align performance with the requirements of related scripts, such as Thuluth script, each with its own unique characteristics, even if they share a unified context. The researchers recommend benefiting from the research findings by including it in the curricula in departments related to the field of Arabic calligraphy to enable the student to be creative in calligraphic achievements. The researchers suggested studying representations of the sustainable design context in Islamic decorative art.